George vi and elizabeth eaudiobook The marriage that saved the monarchy. - Smith, Sally Bedell (Books on Tape, 2023)
A revelatory account of how the loving marriage of King George VI and Queen Elizabeth saved the monarchy during World War II, and how they raised their daughter to become Queen Elizabeth II, based on exclusive access to the Royal Archives—from the bestselling author of Elizabeth the Queen and Prince Charles “An intimate and gripping portrait of a royal marriage that survived betrayal, tragedy, and war.”—Amanda Foreman, bestselling author of Georgiana: Duchess of Devonshire Granted special access by Queen Elizabeth II to her parents’ letters and diaries and to the papers of their close friends and family, Sally Bedell Smith brings the love story of this iconic royal couple to vibrant life. This deeply researched and revealing book shows how a loving and devoted marriage helped the King and Queen meet the challenges of World War II, lead a nation, solidify the public’s faith in the monarchy, and raise their daughters, Princess Elizabeth and Princess Margaret. When King Edward VIII abdicated the throne in 1936, shattering the Crown’s reputation, his younger brother, known as Bertie, assumed his father’s name and became King George VI. Shy, sensitive, and afflicted with a stutter, George VI had never imagined that he would become King. His wife, Elizabeth, a pretty, confident, and outgoing woman who became known later in life as “the Queen Mum,” strengthened and advised her husband. With his wife’s support, guidance, and love, George VI was able to overcome his insecurities and become an exceptional leader, navigating the country through World War II, establishing a relationship with Winston Churchill, visiting Franklin and Eleanor Roosevelt in Washington and in Hyde Park, and inspiring the British people with his courage and compassion during the Blitz. Simultaneously, George VI and Elizabeth trained their daughter Princess Elizabeth from an early age to be a highly successful monarch, and she would reign for an unprecedented seventy years. Sally Bedell Smith gives us an inside view of the lives, struggles, hopes, and triumphs of King George VI and Elizabeth during a pivotal time in history.